The role of "not for profits" (NFPs) in disaster preparedness in Aotearoa New Zealand. Issue 3 (12th January 2021) - Torstonson, Sharon; Blake, Denise; Hodgetts, Darrin; Johnston, David M.
Abstract : Purpose: The purpose of this research is to highlight the role of not-for-profit (NFP) organisations in enhancing disaster preparedness. The authors set out to understand their perspectives and practices in regard to disaster preparedness activities to support people who live precarious lives, especially those who live as single parents who are the least prepared for disasters. Design/methodology/approach: The research draws on in-depth, semi-structured interviews with 12 staff members, either in a group setting or individually, from seven NFP organisations, who were located in Ōtautahi (Christchurch) and Kaiapoi in Aotearoa New Zealand. These participants were interviewed eight years after the 2011 Christchurch earthquake. Findings: Four key narrative tropes or elements were drawn from across the interviews and were used to structure the research results. These included: "essential" support services for people living precarious lives; assisting people to be prepared; potential to support preparedness with the right materials and relationships; resourcing to supply emergency goods. Originality/value: This research contributes to disaster risk reduction practices by advocating for ongoing resourcing of NFP groups due to their ability to build a sense of community and trust while working with precarious communities, such as single parents.